Paciente de 63 años de edad sexo masculino con neumonía de la comunidad. - Jaramillo Maisincho, Lady Julisa (2020)
Pneumonia is a very common pathology characterized by an inflammatory infection of the alveoli that can occur in only one lung or also in both. The present clinical case is a 63-year-old male patient who attends the emergency area due to clinical manifestations such as weakness, fatigue, persistent cough, high fever, greenish sputum and chest pain; A physical examination was carried out and on auscultation, crackles appeared in the right lobe especially, a chest X-ray was performed where a limited and homogeneous condensation could be evidenced, finally he was also ordered to perform a blood culture and a sputum sample where pneumonia resulted. The objective of this case is to identify the clinical manifestations presented by patients with pneumonia in the community and at the same time provide first-time information on the condition. It was concluded that the risk factors that lead to community pneumonia are among the most common an age older than 65 years, an underlying comorbid disease, a macro or micro aspiration, weak immune system, smoking or alcohol; There is no specific therapeutic treatment since it depends on the type and also on the degree of severity of the clinical picture; and if pneumonia is suspected, the tests performed on the patient are a blood test, a chest x-ray, pulse oximetry, and a sputum test.